Phenotypic plasticity in an egg parasitoid affects olfactory response to odors from the plant–host complex - Chierici, Elena; Sabbatini-Peverieri, Giuseppino; Roversi, Pio Federico; Rondoni, Gabriele; Conti, Eric (Frontiers in Ecology and Evolution, 2023)
Female egg parasitoids must optimize their ability to find a suitable host for reproduction in a limited foraging time. Odorant cues associated with the plant-host complex play an essential role in guiding females towards the host. However, parasitoid response is not always identical within the same genotype, and it could be influenced by the environment. Phenotypic plasticity in parasitoid behaviour and morphology is directly linked to rearing conditions. However, how plasticity influences olfactory responses of egg parasitoids towards plant-host odours is largely unexplored. Trissolcus japonicus (Ashmead) (Hymenoptera: Scelionidae) is an effective biocontrol agent of the invasive brown marmorated stink bug, Halyomorpha halys Stål (Hemiptera: Pentatomidae). Laboratory no-choice and choice tests showed T. japonicus potential to develop in eggs of non-target Pentatomidae. The aim of this study was to evaluate the olfactory responses of T. japonicus reared on different hosts towards plant-host derived volatiles associated with H. halys and two other stink bugs. In Y-tube olfactometer, parasitoids reared on the main host H. halys positively responded only to odours from V. faba - H. halys complex. When reared on alternative hosts, T. japonicus were smaller and did not exhibit attraction to any stimuli, while egg load was only partially affected. Host-induced phenotypic plasticity should be considered when evaluating parasitoids for classical biocontrol.